PELATIHAN PPH FINAL PADA UPPKS CEMPAKA DI KAMPUNG KB DUKUH PADANGAN GLODOGAN KLATEN SELATAN - Natalia Ratnaningrum; Inayat Hanum Indriati; Guruh Ghifar Zalzalah; Fikri Farhan; Padrul Jana (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2023)
Efforts to Increase Income for Prosperous Families, which are often referred to as UPPKS, are productive economic business groups, which consist of a group of family members who interact with each other and consist of various stages of prosperous families, both couples of childbearing age who already have family planning and those who have not. stages of well-being and stabilizing. The purpose of this service is to solve UPPKS problems related to taxes, namely calculation, deposit and reporting of Final Income Tax with a certain gross circulation. The method used in this service is that the first service must take into account the Final Income Tax at a rate of 0.5% with the tax base being the gross income in one tax month (Period). After calculating the second is that it must be paid in advance, an ID billing must be made first and later you will get proof of payment in the form of a Tax Payment Slip (SSP) and the last is reporting, reporting can be done through DGT online. The results of this Community Service result in an understanding of theory and practice related to the calculation, payment and reporting of Final Income Tax.